Possibilities of More Flexible Electricity Use in Office Buildings - Hedberg, Fanny (My University, 2015)
The increasing awareness of sustainability issues due to climate change increases the investments in renewable energy. The intermittency and unpredictability of those energy sources will have an impact on the electric power system. The increasing rate of urbanization also makes cities all over the world grow rapidly. To handle this in a sustainable way the energy and resource use must become more efficient. The challenges with renewable energy in the energy system and the demand for more efficient energy use in cities would both be facilitated by a more flexible demand side. This could be enabled by integration of more information and communication technology in the electric grid and in buildings. The purpose of this project is to investigate how office buildings in Sweden can contribute to more efficient electricity use in a city. The overall problem dealt with has been how controlled management of the electricity consumption, solar power production and charging of electric vehicles connected to an office building can be combined to benefit the electric grid while profiting the property owner. There are no technical problems in making the demand side more flexible, and thereby the electric power system more efficient. The challenges lies more in the organizational part and finding business models that make it profitable for all parts involved. The overall problem in realizing these measures at the moment, lies in the fact that there are not yet enough economic incentives since the variations in electricity price, and the electricity price in itself are too low. Some of the changes and possible solutions concerning the energy system depend on societal changes that cannot be fully predicted, thereby creating important uncertainties.
Keywords: Elkraftteknik; Electric power engineering